The Strengths and Weaknesses of Online Learning from The Perspectives of Teachers and Students in Sma/Smk Negeri Buleleng Sub-District During the Covid-19 Pandemic - Pradana, Radita Yuda (International Journal of Language and Literature, 2022)
This research aimed to analyse the strengths and weaknesses of online learning from the perspectives of teachers and students during the COVID-19 pandemic. The subjects of this research were English teachers and students in SMA/SMK Negeri in Buleleng sub-district. In this case, the subjects of the study consist of 21 English teachers including 11 male and 10 female teachers, and 42 students covering 20 male and 22 female students. The data of this research were obtained by using questionnaires. This research is descriptive qualitative research design. The result of this research found that the online learning has strengths and weaknesses according to the perceptions of the teachers and the students.